Layout improvement design to reduce material handling cost by using the systematic layout planning method in the MSME industry - Inaki Maulida Hakim; Durra Salsabila; Keval Priapratama Prajadhiana (Universitas Serang Raya, 2025)
This research discusses layout improvements in MSMEs that produce skin crackers distributed in the Jabotabek area. Currently, the quantity of skin crackers produced is experiencing problems. One of the causes of problems is that material handling is still manual, poor layout settings, limited costs, unpredictable weather and lack of labor availability. Poor material handling causes long production duration, workers are less safe and comfortable, and material handling costs are high. Therefore, this research improved the layout by improving the material handling process. The research aims to analyze the existing layout problems, improve the layout, and compare the existing layout with the proposed layout. The method used to improve the layout is systematic layout planning (SLP). The results of the study are that material handling costs reduced by IDR 256,754.99 or 67.8%, increasing capacity by 17.77 kg per week can solve stock shortages, and the duration of material handling is reduced by 28.95 minutes per day or 69.19%.